Analysis of fracture toughness properties of wire + arc additive manufactured high strength low alloy structural steel components - Dirisu, Philip; Ganguly, Supriyo; Mehmanparast, Ali; Martina, Filomeno; Williams, Stewart W. (Elsevier, 2020)
The uncertainty surrounding the fracture behaviour of CMT-WAAM deposited steel, in terms of crack tip condition (J and CTOD) needed to cause crack tip extension, has made this manufacturing technique unpopular to date. Fracture toughness parameters are crucial in the structural integrity assessment of components and structures in various industries for assessing the suitability of a manufacturing process and material. In the offshore wind industry, the EN-GJS-400-18-LT ductile cast grade for the mainframe and hub has lower fracture toughness resistance for its high strength grade. Its high weight level affects the Eigen frequency of the tower and imposes high installation cost incurred from heavy lifting equipment usage. Poor fracture toughness is currently a challenge for wind turbine manufacturers in the quest for a cleaner and cheaper energy in the form of offshore wind. In this study, CMT-WAAM is used in depositing steel components with an oscillatory and single pass deposition strategy. The effects of microstructural variation, as a result of layer by layer deposition and the layer band spacing, on the fracture resistance in the build and welding direction was shown here. The fracture mechanics and failure mode of the WAAM deposited parts were investigated. The microstructural variation, again as a result of the layer by layer deposition and the layer band spacing, are the key parameters that control the fracture toughness of WAAM steel. Anisotropic behaviour in the values was observed between both fracture orientations. The constructive transformation mechanism of the WAAM oscillatory process made way for intragranular nucleation of acicular ferrite on the Ti containing inclusion, thereby improving the toughness of the ER70S-6 deposit with a unique microstructure and Jq value of 640kJ/m2.
Keywords: High strength low alloy steel (HSLA); CMT wire + arc additive manufacturing (CMT-WAAM); JIC fracture toughness; Layer band spacing; Microstructural variation